SISTEM DISTRIBUSI ONDERDIL KENDARAAN BERMOTOR PADA CV ANUGRAH JAYA MANDIRI BERBASIS JAVA - Hidayatullah, Reko Syarif; Julizal, Julizal; Halimatussa'diah (Universitas Majalengka, 2023)
The purpose of the research is to compile a structured and directed motor vehicle parts distribution information system with. With this distribution information system that is made to be useful and more efficient contained in CV Anugrah Jaya Mandiri. The research used by the author is the Research and Development (R&D) method, which is a research method used to develop or validate products used in education and learning. In this research, data is a source of theory or theory based on data. The selection of application programs made using the Java NetBeans programming language and MySQL as database management, with an interface that is easily understood by the user. Based on the results of the study, the authors conclude that a computerized data management system can make work more effective and efficient, information is faster, more precise and accurate than manual systems, and parts distribution process data is stored in a database.